American women afield : writings by pioneering women naturalists - Bonta, Marcia, 1940- (Louise Lindsey Merrick natural environment series, 1995)
"Armed with hand lenses and opera glasses, traveling on foot, by buggy, or model T, they explored thousands of miles of deserts, forests, beaches, and jungles. They were pioneering women naturalists who observed, studied, and experimented, then returned to write up their findings. What resulted were exquisitely written and scientifically accurate accounts of their explorations into natural science - a field long dominated by men." "Marcia Myers Bonta has collected the most charming and sensitive writings of twenty-five women naturalists of the late nineteenth through early twentieth centuries and supplemented them with well-researched biographical profiles. From Susan Fenimore Cooper's early warnings about the profligate use of natural resources to Mary Treat's tenacious defense of her scientific discoveries, from Alice Eastwood's defiance of convention to Caroline Dormon's, Lucy Braun's, and Rachel Carson's impassioned pleas to save the earth, American Women Afield catalogs the determination and devotion of these early scientists and acknowledges their invaluable contributions to ornithology, entomology, botany, agrostology, and ecology."--Jacket